KAIDAH PENAFSIRAN DAN PERKEMBANGAN PEMIKIRAN TENTANG AL-QUR’AN, TERJEMAH DAN TAFSIR - Dini Apriliani Khairunissa Gurnadi; Muhammad Chirzin (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study examines the principles of Qur'anic interpretation (qawā'id al-tafsīr) and the development of tafsir thought from the classical to the contemporary period. Employing a qualitative library research approach, data were drawn from primary sources such as classical tafsir works and scientific writings, as well as secondary sources including academic journals and theses, and analyzed through content analysis. The findings indicate that sound interpretive principles are essential to preserving the authenticity of Qur'anic meaning and preventing subjective distortion. The evolution of tafsir across periods reflects a dynamic and contextual tradition grounded in the Qur'an and Sunnah, while Qur'anic translation serves as a vital medium for disseminating Islamic teachings globally, albeit inherently interpretive in nature. This study concludes that the study of interpretive principles and Qur'anic translation holds paramount importance in ensuring the Qur'an's enduring relevance as a guide for Muslim life across every generation.